Evaluating The Impact Of Adolescent-Cantered Skill Development Interventions On Psychosocial Attributes And Academic Behaviours: A Systematic Review - Karagi, Mahantesh; Garg, Ram Kumar (Journal of Neonatal Surgery, 2025)
Adolescence is a critical developmental period characterized by significant physical, emotional, and psychological changes. Enhancing psychosocial competencies through adolescent-cantered skill development interventions has become a major focus in education and mental health settings. This systematic review investigates the enhancement of adolescent-centred skill development interventions on psychosocial attributes and academic behaviours such as self-esteem, interpersonal communication, study habits, and adjustment. Total of 30 peer-reviewed studies published between 2015 and 2024 were analysed from databases such as PubMed, Scopus, and Google Scholar using PRISMA guidelines. The evidence suggests that adolescent-centred skill development interventions significantly enhance self-esteem, improve interpersonal communication skills, foster effective study habits, and aid adolescents in adapting to various social and academic environments. This review advocates for the integration of life skills related training programmes into school curricula to address holistic adolescent development.